Involvement of Inflammatory Mediators in the Gastroprotective Action of Phaleria macrocarpa against Ethanol-Induced Gastric Ulcer - Abood, W.N.; Abdulla, M.A.; Ismail, S. (IDOSI Publications, 2014)
This research aimed to determine the potential protective effects of Phaleria macrocarpa fruit extracton rat gastric mucosal injury induced by ethanol andto clarify the roles of prostaglandinE2 (PGE2), transforming growth factor-1 (TGF-) and tumor necrosis factor- TNF-). Main methods: Seven groups of rats were orally pretreated with Tween20 as vehicle control group; Tween20 as ulcer group; 20 mg/kg of omeprazole as reference drug group; and100, 200,500 and 1000 mg/kg of extract as experimental groups. An hour later, ulcer was induced by oral administration of 95% ethanol, except in the vehicle control group.Results showed significant ulcer protective effects through reduction of ulcer area and increase of ulcer inhibition by significant elevation ofgastricpH and increase ofmucus production. In addition, significant increasein levels of inflammatory mediators PGE2 and TGF-1 and decrease in TNF- were observed in the groups pretreated with P. macrocarpa compared with ulcer control group. In conclusion,our results suggested that P. macrocarpa pretreatment has protective effects against ethanol-induced gastric ulcers in rats by significantly stimulating inflammatory mediators PGE2, TGF-1 and reducing TNF- which effect in the increase production of mucus and stomach pH to provide a protective environment against the offensive factors.